Books Review on Pokoknya Sunda: Interpretasi untuk Aksi; Pokoknya Rekayasa Literasi; Language, Culture, and Education: A Portrait of Contemporary Indonesia - Dasep Suprijadi (Eltin Journal : Journal of English Language Teaching in Indonesia, 2014)
This review examines three Alwasilah’s books entitled: 1) Pokoknya Sunda: Interpretasi untuk Aksi; 2) Pokoknya Rekayasa Literasi; and 3) Language, Culture, and Education: A Portrait of Contemporary Indonesia.  The reviewer endeavors to evaluate the author’s point of view and the contents of the books supported by a set of extant theories dealing with the similar issues.  These books are designed as a set of foundations and learning materials of some subjects taught by the author. The author explores the insight concerning various contemporary issues dealing with policy, literacy, language as well as culture and education in this beloved country, Indonesia.